Design of Telegram Bots for Campus Information Sharing - Setiaji, H. (Institute of Physics Publishing, 2018)
This paper presents a design of Telegram bot to support Campus information sharing. The communication method used is Webhooks. Webhooks is able to provide zero latency and handle multiple requests concurrently during communication within the Telegram bot. Such bot serves the information via specific commands. The Telegram bot prototype shows that even though Webhooks is able to provide information as requested, Webhooks setting is difficult and trickier. Â© Published under licence by IOP Publishing Ltd.